Sustainability and Resilience Planning for Local Governments The Quadruple Bottom Line Strategy - Alibašić, Haris (Sustainable Development Goals Series,, 2018)
This book details a process of creating long-term sustainability and resilience plan for local governments to use for designing and implementing sustainability and resilience policies, initiatives, and programs. It offers guidance, strategies, and methods in applying sustainability and resilience planning to attain the prosperity of organizations and communities. The recommendations in this book are based on the author's years of direct experience in directing applied resilience and sustainability planning for a local government, and years of research covering diverse aspects of sustainability and resilience from climate change, climate preparedness and readiness, triple bottom line impact, quadruple bottom line strategy, carbon footprint and greenhouse gas emission policies, climate adaptation and climate change mitigation to sustainable energy policies and practices. Chapter one defines terms related to sustainability and resilience, how the topics reshape local governments and communities. Chapter two maps out the sustainability process for organizations and communities, determining the appropriate steps to be taken at each level of sustainability and resilience planning. Chapter three identifies community and organizational level engagement, internal and external stakeholders, including designs necessary throughout these processes. Chapter four involves measuring, tracking, monitoring and reporting using the quadruple bottom line strategy, and developing a sustainability and resilience progress report to ensure accountability, transparency, and good governance. Then, chapter five details the implementation of a sustainability/resilience plan once it is established, describing potential programs and initiatives to achieve sustainable and resilient communities. Chapter six describes the intersection between sustainability and resilience, and chapter seven examines the tools and resources available to create effective sustainability and resilience plan. Chapter eight concludes the text by addressing the future of sustainability and resilience, and complexities of the modern dynamics of the interconnected systems in cities, counties, and organizations, and recommends how local government administrators in their planning methods and strategies must consider these challenges.